Radiation tolerant implementation of a soft-core processor for space applications - Van der Horst, Johannes Gerhardus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.